2018
DOI: 10.1111/ecot.12156
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal structure, risk‐taking and firm value

Abstract: This article investigates the relationship among pyramidal layers, risk‐taking and firm value using a sample of local state‐owned enterprises (SOEs) in China. We find that state‐pyramidal layers have a positive and significant impact on firm risk‐taking and firm value, suggesting that the pyramidal structure formed by the state protects SOEs from political intervention. Risk‐taking is conducive to enhancing firm value and is one of the important channels through which state‐pyramidal layers increase firm value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Among academic investigations of antecedents to risk‐taking, the impact of corporate governance structure as it relates to risk taking has become a topic of growing interest (Su & Liu, ). Arguments supporting the role of corporate governance structure include classical theories such as the principle‐agent perspective (Chen & Zheng, ), stakeholder theory (Cziraki & Xu, ), and principle‐principle viewpoint (Boubakri, Cosset, & Saffar, ; Su et al, ; Su, Wan, & Song, ). However, relatively few studies have focused directly on corporate boards although they are the key corporate governance mechanisms affecting risk taking choices.…”
Section: Introductionmentioning
confidence: 99%
“…Among academic investigations of antecedents to risk‐taking, the impact of corporate governance structure as it relates to risk taking has become a topic of growing interest (Su & Liu, ). Arguments supporting the role of corporate governance structure include classical theories such as the principle‐agent perspective (Chen & Zheng, ), stakeholder theory (Cziraki & Xu, ), and principle‐principle viewpoint (Boubakri, Cosset, & Saffar, ; Su et al, ; Su, Wan, & Song, ). However, relatively few studies have focused directly on corporate boards although they are the key corporate governance mechanisms affecting risk taking choices.…”
Section: Introductionmentioning
confidence: 99%
“…The level of risk-taking reflects the ability of enterprises to grasp financing opportunities [78]. Moreover, higher risk-taking is conducive for enterprises to grasp investment opportunities with higher returns [29,59] to achieve a long-term competitive advantage.…”
Section: Further Analysismentioning
confidence: 99%
“…As this study draws on group decision‐making theory, it is pertinent to consider the role of firm risk taking (Nakano & Nguyen, ; Su et al, ). Prior research has shown that risk taking has a positive impact on firm value (Su, Wan, & Song, ). Risk taking has also been shown to affect the efficiency of the firm's capital allocation (Durnev, Morck, & Yeung, ), growth (Campbell, Lettau, Malkiel, & Xu, ; Kim, ), and technological innovation (García‐Granero, Llopis, Fernández‐Mesa, & Alegre, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%